The Role of Stearoyl-coenzyme A Desaturase 1 in Liver Development, Function, and Pathogenesis (Journal of Renal and Hepatic Disorders, 2019)
Stearoyl-coenzyme A desaturase 1 (SCD1) is a microsomal enzyme that controls fatty acid metabolism and is highly expressed in hepatocytes. SCD1 may play a key role in liver development and hepatic lipid homeostasis through promoting monounsaturated protein acylation and converting lipotoxic saturated fatty acids into monounsaturated fatty acids. Imbalanced activity of SCD1 has been implicated in fatty liver induction, inflammation and stress. In this review, the role of SCD1 in hepatic development, function and pathogenesis is discussed. Additionally, emerging novel therapeutic agents targeting SCD1 for the treatment of liver disorders are presented.
Keywords: hepatic lipogenesis; hydroxy pyridine; MK-8245; stearoyl-coenzyme A desaturase 1; SCD1